Metal‐Free Epoxidation of Internal and Terminal Alkenes with tert‐Butyl Hydroperoxide/Isobutyraldehyde/Oxygen System. Issue 17 (3rd May 2018) - Hong, Mei; Min, Jie; Wang, Shifa
Abstract: The epoxidation of several alkenes was studied using oxygen as green oxidant, isobutyraldehyde (IBA) as co‐reagent and tert‐butyl hydroperoxide (TBHP) as radical initiator at mild conditions (60 o C, atmospheric pressure with an oxygen balloon). TBHP could accelerate the production of carbonyl radical and its peroxidation, without using a metal catalyst. The factors influencing the conversion of the substrates and selectivity of the epoxides have been well investigated. Under optimized reaction conditions, the epoxidation of linear terminal, cyclic and aromatic alkenes was evaluated. Most performed reactions were high selectivity for production of the corresponding epoxides. Abstract : A cheap, mild and fast oxidation of olefins to the corresponding epoxides is reported using oxygen as oxidant, tert‐butyl hydroperoxide (TBHP) as radical initiator at ambient pressure and moderate temperature in the presence of isobutyraldehyde (IBA).